The Effect of Massed Practice and Distributed Practice on Free Shots for Men's Junior Basketball Athletes at Warrior Club Kepahiang District - Andi Wijaya Putra Tama (Hanoman Journal: Physical Education and Sport, 2021)
This study is an experiment that aims to identify different effect of massed practice exercises and distributed free practice on free shots the son of a junior basketball club athletes galaxy Padang Panjang. The hypothesis of this research are: 1) There is the effect of massed practice exercises on free shots. 2) There is a distributed practice effect of exercise on free shots. 3) There are differences in the effect of massed practice exercises and distributed free practice of firing the son of a junior basketball club athletes Warrior Club Kepahiang District. The population in this research is the son of club basketball athletes Warrior Club Kepahiang District totaling 70 people, because according to the needs of this research, the junior son of an active athlete exercises, the samples used were 20 people with a purposive sampling technique sampling. After the pre test all the samples were divided into two groups by the total ordinaly pairing techniques. Both groups consisted of massed practice group practice and distributed practice. Each group consisted of 10 persons. The experiment consisted of 18 sessions, a week exercise conducted as many as four times. The duration of the exercises in each season is 90 minutes. The test results of pre-post test which was recorded is the result of free shots in after 10 shot attempts. Based on data analysis, it can be concluded that: 1) There is significant effect of massed practice exercises on free shots which average 4.10 (pre test) to 5.40 at post test, where t = 3.88 ttable = 2.26. 2) There were no significant effects of distributed practice on free shots an average of 4.20 (pretest) to 4.40 at post test, where t = 0.80 ttable = 2.26. Thus, the first and the third hypothesis received while the second hypothesis is rejected.